Alternative Technologies for Marine-Coastal Environment Debris Monitoring: A Review - Mia Galina; Cutifa Safitri (President University, 2021)
Abstract: The problems in the marine and coastal environment have aroused the attention of many countries in the world. According to [1], it is estimated that every year eight million tons of debris find their way into the world's oceans, thus disturbing aquatic and marine ecosystems. Particularly in the case of coastlines, many studies show that the majority of marine litter (60-80%) consists of plastic [2]. The objectives are to evaluate the critical issues in regards to marine environment waste monitoring and to track the development of technology used in the field of marine and coastal debris monitoring problems over the last two decades. The method of this research is by investigating the topic that is quite a lot raised as research related to coastal and marine waste and the distribution of technology implemented for coastal and marine debris. The results show that waste in coastal and marine areas is a problem that needs to be solved immediately. The data relating to the generation of waste flowing into the ocean is dynamic, moving every day, depending on the generation of the generated waste and its accumulation and drifting in the ocean. The large amount of information collected from higher views (such as satellite views) provides important insights for understanding and identifying plastic waste debris pollution and its movement. The conclusion: Regardless of the application, an integrated technical solution is required, which can be sensors, communication devices, data packet transmission from client devices to servers with appropriate application protocols, or a combination of several technologies